Co-Translational Folding of Multi-Domain Proteins - Rajasekaran, Nandakumar; Kaiser, Christian M. (Frontiers in Molecular Biosciences, 2022)
The majority of proteins in nature is composed of multiple domains connected in a single polypeptide. How these long sequences fold into functional structures without forming toxic misfolds or aggregates is poorly understood. Multi-domain protein folding is inextricably linked to protein synthesis and to interactions with cellular machinery, making mechanistic studies challenging. Recent progress has revealed critical features of multi-domain protein folding in isolation and in the context of translation by the ribosome. In this review, we discuss challenges and progress in understanding multidomain protein folding, and highlight how molecular interactions shape folding and misfolding pathways. With the development of new approaches and model systems, the stage is now set for mechanistically exploring the folding of large multi-domain proteins.